Implementation of Geographic Information System (GIS) And Multi-Criteria Decision Analysis (MCDA) In Determining Tourist Attractions In Samosir Regency - Adelina Manik; Ilka Zufria (Cattleya Darmaya Fortuna, 2026)
Tourism in Samosir Regency has significant potential as a key sector in North Sumatra Province; however, there is an imbalance in the number of visitors across various tourist sites. This study aims to develop a decision support system for identifying and prioritizing tourist destinations based on accessibility and traveler preferences by integrating Geographic Information System (GIS) and Multi-Criteria Decision Analysis (MCDA) using the Analytical Network Process (ANP) approach. The system utilizes both spatial and non-spatial data to map tourist locations and determine priorities based on relevant criteria such as accessibility, distance, cost, attractiveness, and safety. The results show that Bukit Sibea-Bea emerges as the leading tourist destination with the highest priority weight (12.45%), followed by Godang Beach and Paromasan. The web-based system provides not only accurate geographical information but also recommends the best tourist destinations based on traveler preferences, making it a useful tool for more targeted and equitable tourism planning and development in Samosir Regency.